"Colorful" Approach Regarding Creative Accounting. An Introspective Study Based On the Association Technique - Diana Elisabeta Balaciu; Victoria Bogdan; Liliana Feleaga; Adela-Laura Popa (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The research aims to make an introspection of the irrational behavior of the managers who, being under the pressure of sending as favorable as possible signals to different categories of users regarding the enterprise they manage, are tempted to use creative accounting techniques. The research is based on the administration of a questionnaire to Romanian managers from Bihor county. Wishing to detect as favorably as possible the way in which the managers perceive and develop their relations with auditors and accountants, we have used in making up the questionnaire, a research method from the category of projective techniques, the free association technique. We found out that more than half of sampled managers are inclined to change an accounting policy that brings major benefits to the firm's image and also there is an aversion towards risk among managers in Bihor, yet it is doubled by their tendency towards accounting manipulation. The projective techniques chosen have led us then to carry out two polar diagrams which detect the managers' perception regarding auditors and accountants.
Keywords: M41; 650; Creative accounting; managers; projective techniques; performance; options; animal spirits